Chemistry students’ beliefs, educational experiences and perceptions of teaching as a future profession: A case study in Serbia - Dušica Rodić; Saša Horvat; Ivana Bogdanović; Malina Popović; Tamara Rončević (Macedonian Journal of Chemistry and Chemical Engineering)
Teaching is one of the most important professions. However, these days there is a significant decrease in enrolment in educational programs, especially in science subjects such as chemistry, physics, and mathematics. For this reason, studying chemistry students' perspectives is valuable. This study examines the beliefs of 57 chemistry students in Serbia. They were asked questions about experience with chemical experiments in schools, the unpopularity of chemistry and incentives for enrollment in chemistry studies, teachers' competencies and chemistry education subjects, advantages, disadvantages and opinions about the teaching profession. The study used a 20-question questionnaire, and participation was voluntary and completely anonymousThe results of the research show that in primary and secondary schools, the lack of laboratory exercises and the abstract nature of chemistrycontribute to the unpopularity of chemistry. Benefits gained after completing studies, such as increased salary and social standing, could improve enrollment in chemistry education programs.